Use of Dried Distillers’ Grains with Solubles in Growing-finishing Diets of Turkey Hens - Roberson, Kevin D. (International Journal of Poultry Science, 2003)
Two experiments were conducted with Large White female turkeys to evaluate the effect of dried distillers` grains with solubles (DDGS) derived from ethanol production on growth performance from about 8 to 15 wk of age. Experiment 1 consisted of inclusion levels of 0, 9, 18 or 27% DDGS to a corn-soybean meal based diet and the treatment diets were formulated with a metabolizable energy value of 2870 kcal/kg for DDGS and on a digestible amino acid basis. The grower diet was fed from 56 to 77 d of age and the finisher diet was fed from 77 to 105 d of age. Body weight was linearly decreased at 105 d as % DDGS increased in the diet. Feed conversion was increased at p = 0.100 from 77 to 105 d of age as DDGS inclusion level increased. The incidence of pendulous crops increased when high levels of DDGS were fed. In Experiment 2, dietary treatments consisted of 0, 7, or 10% DDGS in the grower period. Half of the birds fed 10% DDGS in the grower period were fed 7% DDGS in the finisher period. The mash diets were formulated with a metabolizable energy value of 2805 kcal/kg for DDGS and on a total amino acid basis. There were no significant effects on body weight or feed conversion in Experiment 2. Results indicate that ethanol-derived DDGS can be effectively included at 10% in growing/finishing diets for turkey hens if proper formulation matrix values for all nutrients are used.